Hindrance effect of tides on water exchanges between the Red Sea and the Gulf of Aden - Guo, Daquan; Yao, Fengchao; Zhan, Peng; Krokos, George; Hoteit, Ibrahim (Frontiers in Marine Science, 2022)
As a semienclosed marginal sea, the Red Sea connects with the open ocean through a narrow strait at its southern end, known as the Bab-al-Mandeb (BAM) strait. The water exchange between the Red Sea and the Gulf of Aden at the BAM strait is crucial for the water mass transformations and thermohaline circulation in the Red Sea as well as for nutrient supply to the open ocean. In this study, a three-dimensional high-resolution nonhydrostatic MIT general circulation model (MITgcm) was used to investigate the tidal influence on the water exchange in the BAM strait through simulations with and without tidal forcing. We found that the tidal effects on the water exchange in winter were insignificant; however, the summer intrusion of the Gulf of Aden Intermediate Water (GAIW) was strongly affected. When the simulation includes tidal forcing, the along-axis northern extension of the GAIW intrusion is reduced by up to 100 km and the monthly mean volume transport is decreased by 20% on average. Two factors that possibly contribute to the hindrance effects of tides in summer are (i) the tidal residual currents that propagate in a direction opposite to the pathway of the GAIW intrusion currents and (ii) the enhanced vertical mixing at the pycnocline and near the benthic topography of the BAM strait, which triggers more instabilities along the pathway of the intrusion.